A Semiotic Analysis of Batu Padas Stone Sculpture Craft in Sukawati District - I Wayan Arissusila; Ni Luh Putu Trisdyani; I Ketut Gede Rudita (Institut Bisnis dan Teknologi Indonesia, 2025)
The batu padas stone sculpture craft is a form of traditional visual art that continues to develop and be preserved in Sukawati District, Gianyar Regency, Bali. Various religious-themed sculptures, such as those depicting Goddess Saraswati, Shiva, and Ganesha, are produced sustainably and demonstrate strong visual appeal. This phenomenon indicates that batu padas sculptures do not merely exhibit aesthetic qualities but also embody symbolic meanings constructed through a system of signs. This study aims to analyze the symbolic meanings of batu padas stone sculptures through the relationship between signifier and signified based on Ferdinand de Saussure’s semiotic theory. The research employs a descriptive qualitative method, with data collected through observation, interviews with local artisans, and documentation studies. Data analysis is conducted by identifying visual elements of the sculptures as signifiers that refer to specific signified concepts, followed by an interpretation of the resulting symbolic meanings. The findings reveal that batu padas stone sculptures form an interconnected system of signs representing aesthetic and religious values. Thus, these sculptures function not only as artistic objects but also as meaningful visual media within Balinese Hindu culture.